INDONESIA'S ECONOMIC DIPLOMACY STRATEGY IN NAVIGATING US-CHINA COMPETITION IN THE INDO-PACIFIC REGION: RECOMMENDATIONS FOR POLICY MAKERS - Gatari Dwi Hapsari; Ghiyats Akmaluddin; Desi Hardjianti Waode; Reynaldi Ramadhani (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2025)
The intensifying strategic tensions between the United States and China in the Indo-Pacific region have created both challenges and opportunities for Indonesia's economic development. This article examines Indonesia's economic diplomacy strategy as a form of hedging to navigate this great power rivalry while maximizing national interests. Using qualitative case study methodology, this research analyzes policy documents, official speeches, economic reports, and secondary literature from the Jokowi administration period (2014-2024). The findings reveal that Indonesia implements a complex economic hedging strategy, combining soft balancing toward both China and the United States through cooperation with Quad nations, while simultaneously engaging in economic bandwagoning by attracting investments and participating in the Belt and Road Initiative. This dual approach allows Indonesia to maintain strategic autonomy and leverage economic benefits from both competing powers. The study concludes that Indonesia's economic diplomacy has been relatively successful in mitigating risks and capitalizing on opportunities, though it faces sustainability challenges and deepening geopolitical pressures. The research contributes to understanding modern non-aligned practices in economic contexts and provides policy recommendations for maintaining strategic flexibility in an increasingly polarized regional order.